Biotechnological valorization of sugar beet wastes into value-added products - Azhar Makambai Kyzy; Aichurok Mazhitova (MANAS: Journal of Engineering)
The sugar beet processing in the sugar production industry releases huge amounts of sugar beet pulp, lime residue, and molasses, which can be considered a valuable by-product as a source of cellulose, hemicellulose, and pectin. Sugar beet pulp is often used as a high-energy, low-protein supplement for ruminants to promote optimal rumen health and increase milk production. However, it cannot be used in large quantities and is thrown away, causing environmental pollution. Valorizing sugar beet processing wastes via biotechnological approaches into value-added products is cost-effective and eco-friendly. In this article, recent developments in the biotechnological valorization of sugar beet byproducts to produce biofuels, bioethanol, butanol, biomass and platform chemicals such as gluconic acid, lactic acid, rhamnolipid biosurfactant, and endo-polygalacturonase were reviewed, and the methods provide a way to save the environment. Several sugar beet processing plants in the Kyrgyz Republic can offer these methods as a roadmap for value-added production.